Efficiency in Covid-19 Vaccination Campaigns – A Comparison across Germany's Federal States - Georg Goetz; Daniel Herold; Phil-Adrian Klotz; Jan Schäfer (Philipps-University Marburg, School of Business and Economics, 2021)
This article investigates the efficiency of the roll-out of Covid-19 vaccinations when vaccines are scarce. Using Germany as an example, we find considerable differences across federal states in terms of efficiency, defined as the ability to get most vaccinations out of a given number of available doses. Back-of-the-envelope calculations for the past five months show that vaccinations would have been 3.7–6.6% higher if all federal states had adopted a similar ratio between vaccinations given and vaccines stored as the most efficient ones. We also find evidence that the integration of doctor's offices into the vaccination campaign significantly increased the share of vaccinations out of a given stocks of vaccine doses.
Keywords: 330